Clinical significance of pectoralis muscle strength in elderly patients with idiopathic pulmonary fibrosis: Pectoralis muscle strength in IPF - Durdu, Habibe; Yurdalan, Saadet Ufuk; Ozmen, Ipek (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Introduction: Investigations of muscle dysfunction in patients with idiopathic pulmonary fibrosis (IPF) are limited to peripheral muscles. However, decreased thoracic muscle mass is known and deterioration of chest wall muscle strength is not clear. Objective: The aims of the present study were to evaluate pectoralis muscle strength located on the chest wall and to investigate the relationship of spirometric measurements and respiratory muscle strength with pectoralis muscle strength. Methods: Elderly patient with IPF (mean disease duration 7.47±7.04 years) and the age-and sex-matched healthy volunteers were recruited in this cross-sectional study. The pulmonary function test was performed by a portable spirometer for spirometric variables and a gas analyzer for diffusing capacity for carbon monoxide (DLCO). Maximal inspiratory (MIP) and expiratory pressure (MEP) were measured with mouth pressure device. Modified Medical Research Council Dyspnea Scale (MMRC) was used to determined dyspnea severity. The pectoralis muscle strength was assessed isometrically during shoulder joint horizontal adduction movement with a handheld dynamometer. Results: A total of 17 patients with IPF (9 males, mean age 69.06±3.94years) and 19 healthy controls (10 males, mean age 70.95 ±4.99years) were included. Patients with IPF had lower pectoralis muscle strength than healthy controls (p